2020
DOI: 10.1177/0308022620902683
|View full text |Cite
|
Sign up to set email alerts
|

The effect of HIV status on post-stroke outcomes in personal activities of daily living

Abstract: Introduction This study explored the impact of HIV on the functional recovery of personal activities of daily living of stroke survivors. This assisted in identifying possible implications for the rehabilitation of stroke survivors who are also HIV-positive. Method A quantitative, descriptive, longitudinal comparative research design was used to determine the change in personal activities of daily living scores of HIV-negative and HIV-positive stroke survivors from admission to 1 month after discharge. Data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…Peminggiran sosial pula menyebabkan PHW sentiasa dipulau, disisih dan dihalau dan meletakkan mereka dalam tekanan berpanjangan, kecewa dan marah. Situasi dialami PHW ini semakin parah apabila keupayaan dalam aktiviti harian semakin terbatas dan mengalami pelbagai komplikasi kesihatan lain (Augustyn, Witt & Franzsen, 2020). Manakala di luar lingkungan keluarga pula, PHW tidak diberi peluang pekerjaan, distigma dan didiskriminasikan, dituduh dengan pelbagai gelaran negatif dan dinafikan segala hak yang sepatutnya mereka dapat.…”
Section: Pengenalanunclassified
“…Peminggiran sosial pula menyebabkan PHW sentiasa dipulau, disisih dan dihalau dan meletakkan mereka dalam tekanan berpanjangan, kecewa dan marah. Situasi dialami PHW ini semakin parah apabila keupayaan dalam aktiviti harian semakin terbatas dan mengalami pelbagai komplikasi kesihatan lain (Augustyn, Witt & Franzsen, 2020). Manakala di luar lingkungan keluarga pula, PHW tidak diberi peluang pekerjaan, distigma dan didiskriminasikan, dituduh dengan pelbagai gelaran negatif dan dinafikan segala hak yang sepatutnya mereka dapat.…”
Section: Pengenalanunclassified
“…Personal ADL is also the focus of another study in this special edition; a South African cohort study examining the one month personal ADL outcomes of stroke survivors infected with HIV (Augustyn et al, 2020), which observed a decline in personal care in infected versus non-infected patients. Like audit, these observational data can highlight a problem (identify evidence) or and inform the development of an intervention (identifying or developing theory).…”
Section: How Do They Do This?mentioning
confidence: 99%
“…These numbers are 1.5 times higher and 22 years younger than the general U.S. population [14]. Augustyn et al recently showed that stroke survivors with HIV experienced a decline in ADL functions one month after discharge compared to stroke survivors without HIV who continued to show improvement, highlighting how HIV can impact stroke recovery [15].…”
mentioning
confidence: 99%